Probing the active site in single-atom oxygen reduction catalysts via operando X-ray and electrochemical spectroscopy - Hsiang-Ting Lien (Nature Portfolio, 2020)
Understanding active-site geometry and structural evolution during electrocatalysis is important for further development. Here the authors use operando X-ray absorption spectroscopy combined with electrochemical impedance spectroscopy to investigate single atom catalysts derived from Vitamin B12.